Tension Butt Joints with Bolts and Welds in Combination - Jarosch, K.H.; Bowman, Mark D. (Engineering Journal, 1986)
Combination joints, also known as load-sharing joints, are connections that use a combination of high-strength bolts and structural welds. Two different types of combination joints are used occasionally in the fabrication of steel structures: shear splices where the bolts and welds share the load on a common shear plane, and connections where the bolts and welds are used on shear planes that are not common. The former type of connection is used sometimes when repairing or modifying a connection; the welds are compact and can be easily added to an existing high-strength bolted connection to provide additional strength. The latter connection type is commonly used in steel beam-column joints. Tests described in this paper provide information on the strength and load interaction characteristics of combination joints for a variety of weld and bolt configurations. The studies include an evaluation of methods currently available for predicting the ultimate tensile strength of combination joints. The combination joints examined in the study are limited to butt joints which use bolts and welds on a common shear plane.